PEMBERDAYAAN KELOMPOK PETANI DISABILITAS MELALUI PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR - Mecilita, Inas; Dianeta, Dianeta; Hamdayani, Peri; Pangaribuan, Angelia Anggita; Oktavia, Serli; Kusumawardhani, Ilma Yukha; Mustiko, Cahyo (Universitas Mataram, 2024)
Real Work Lectures (KKN) is a form of application of the Tri Dharma of Higher Education, namely community service. This activity was carried out in Taman Ayu Village, Gerung District, West Lombok Regency which is known for its abundant natural resource potential where the majority of the population's livelihood is farming and animal husbandry. This is no exception for groups of people with disabilities who often find it difficult to find work and choose farming as an alternative. Seeing this, the 2024 Mataram University PMD KKN group took the initiative to empower groups of farmers with disabilities through outreach and training in making liquid organic fertilizer from aloe vera. The method of implementing this activity consists of two stages, namely the planning stage and the socialization and training stage. The results of this activity showed high enthusiasm from the participants. It is hoped that this activity can increase crop production, provide ideas for new business opportunities, and support the welfare of disabled farmers in Taman Ayu Village